Are There Mutator Polymerases? - Miguel Garcia-Diaz; Jose F. Ruiz; Raquel Juarez; Gloria Terrados; Luis Blanco (The Scientific World Journal)
DNA polymerases are involved in different cellular events, including genome replication and DNA repair. In the last few years, a large number of novel DNA polymerases have been discovered, and the biochemical analysis of their properties has revealed a long list of intriguing features. Some of these polymerases have a very low fidelity and have been suggested to play mutator roles in different processes, like translesion synthesis or somatic hypermutation. The current view of these processes is reviewed, and the current understanding of DNA polymerases and their role as mutator enzymes is discussed.